2001
DOI: 10.4049/jimmunol.167.6.3308
|View full text |Cite
|
Sign up to set email alerts
|

ATP Stimulates Human Macrophages to Kill Intracellular Virulent Mycobacterium tuberculosis Via Calcium-Dependent Phagosome-Lysosome Fusion

Abstract: Advances in therapy for tuberculosis will require greater understanding of the molecular mechanisms of pathogenesis and the human immune response in this disease. Exposure of Mycobacterium tuberculosis-infected human macrophages to extracellular ATP (ATPe) results in bacterial killing, but the molecular mechanisms remain incompletely characterized. In this study, we demonstrate that ATPe-induced bactericidal activity toward virulent M. tuberculosis requires an increase in cytosolic Ca2+ in infected macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(117 citation statements)
references
References 47 publications
1
115
1
Order By: Relevance
“…Confocal microscopy shows P2X7 in the phagosome membrane surrounding engulfed particles or bacteria [29,30] and recent reports suggest that P2X7 together with pannexin-1 may facilitate the delivery of bacterial products from phagosome lumen into the cytosol, where they can activate inflammasome assembly [31,32]. Moreover P2X7 has a role in facilitating the fusion of phagosome with lysosome by a process involving stimulation of phospholipase D activity presumably on the phagolysosomal membrane [33,34].…”
Section: Non-opsonized Beadsmentioning
confidence: 94%
“…Confocal microscopy shows P2X7 in the phagosome membrane surrounding engulfed particles or bacteria [29,30] and recent reports suggest that P2X7 together with pannexin-1 may facilitate the delivery of bacterial products from phagosome lumen into the cytosol, where they can activate inflammasome assembly [31,32]. Moreover P2X7 has a role in facilitating the fusion of phagosome with lysosome by a process involving stimulation of phospholipase D activity presumably on the phagolysosomal membrane [33,34].…”
Section: Non-opsonized Beadsmentioning
confidence: 94%
“…1A). Differentiation of THP-1 and U937 cells to a macrophage-like phenotype by incubation with IFN-␥, 1,25-dihydroxyvitamin D 3 , and retinoic acid (16,45,46), resulted in increased levels of both PLD1 and PLD2 in U937 cells, but no significant change was noted in THP-1 cells (Fig. 1A).…”
Section: Primary Human Macrophages and Myelomonocytic Cell Lines Exprmentioning
confidence: 97%
“…On a follow up of this work (Fairbairn et al, 2001), the same group showed that ATP treatment of infected macrophages led to an increase of fusion between phagosomes and lysosomes and further confirmed the ability to dissociate anti-mycobacterial activity from apoptosis. Similarly, Kusner & Barton (2001) Infection of macrophages and induction of apoptosis. After 9 days in culture, macrophages were incubated with a mycobacterial suspension of M. avium strain 25291.…”
mentioning
confidence: 99%